A A Review on E-Ball Technology (International Journal of Engineering and Computer Science, 2018)
We all are familiar with the word computer, and we all know that earlier computer was huge in size. Day by day the size of computer reduces and   now a new concept of PC is introduced that is E-Ball Concept pc. The E-Ball concept PC is the smallest design among all the laptops and desktops. E-ball is design by “Apostol Tnokovski”, a 31 year old Macedonian product designer. He has replaced the old PC from the squares and rectangular shape with his newly designed wonder in a spherical shape. According to Apostol it is the best shape in nature and it draws everybody’s attention. It is the smallest PC ever made. The size of E-ball is just like a ball, we can keep in our pocket and move from one place to another. This PC contain everything in-built like keyboard, mouse etc. This PC concept features all the traditional elements like mouse, keyboard, large screen display, DVD recorder; speaker etc. It is yet to be launched in market. The research in this field is still going on.